Marginal Adaptation and Depth of Cure of Flowable versus Packable Bulk-fill Restorative Materials: An In Vitro StudyMarginal Adaptation and Depth of Cure of Flowable versus Packable Bulk-fill Restorative Materials: An In Vitro Study - Abdelwahed, Ahmed Gamal; Essam, Shereen; Abdelaziz, Monaliza M. (Open Access Macedonian Journal of Medical Sciences, 2022)
Aim: To investigate the marginal adaptation and depth of cure of a flowable bulk-fill giomer (BEAUTIFIL Flow Plus X [BFP]), a flowable bulk-fill resin composite (PALFIQUE BULK FLOW [PBF]) bulk-fill resin composite, a packable bulk-fill giomer (BEAUTIFL-Bulk Restorative [BBR]), and two packable bulk-fill resin composites (X-tra fil [XF]) and (Filtek™ One Bulk Fill Restorative [FOB]). Materials and Methods: Twenty-five standardized class II cavities were prepared in the occlusomesial surfaces of maxillary premolars. A self-etching dental adhesive was used. All restorative materials were applied, and light cured according to their manufacturer’s instructions. The teeth were subjected to 2500 thermal cycles between 5° C and 55° C. Epoxy resin replicas were obtained to examine the marginal by calculating the percentage of the continuous margin over the total margin length. using SEM at 200× magnification. For assessing the depth of cure, fifty specimens with 4 mm height were prepared. Vickers microhardness testing was used to assess the depth of cure was calculating the bottom-to-top ratio of each specimen. If this ratio reaches 0.80 or more, an adequate depth of cure is achieved. Results: Regarding marginal adaptation, there was no significant difference between different groups before (p=0.398) and after (p=0.644) thermocycling. Within all groups, there was a significant decrease in marginal adaptation after thermocycling (p<0.001). Regarding the depth of cure, all restorative materials achieved the required 0.8 bottom-to-top ratio. There was a significant difference between different groups (p<0.001). The highest value was found in BFP group (0.97±0.02), while the lowest value was found in BBR group (0.81±0.11). Conclusions: The marginal adaptation and depth of cure of bulk-fill giomer restorative materials are acceptable. Therefore, their use in restoration of 4-mm deep class II cavities is appealing.